New Service Development: Innovation in Information Equity Through the Public Information Openness Ambassador Program at the Information and Documentation Management Officer of State Islamic University Sunan Gunung Djati Bandung - Fadjar Tri Sakti; Ludiana; Muhammad Ilham Septianan; Putri Rabbani Kurnia; Raissya H Danies K; Wangsa Merta Kusuma (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
UIN Sunan Gunung Djati Bandung, as a public service institution, must provide excellent public services, especially in information distribution. However, there are still inconsistencies in delivering important information, particularly to students. Therefore, innovation in New Service Development of the Public Information Disclosure Management (PPID) at UIN Sunan Gunung Djati Bandung is needed through the Public Information Disclosure Ambassador program to overcome barriers and improve the efficiency of information dissemination on campus. This research aims to analyze the effectiveness of the Public Information Disclosure Ambassador program in enhancing information distribution at UIN Sunan Gunung Djati Bandung. The research method used is a qualitative approach that is descriptive in nature, utilizing data collection techniques in the form of interviews, observations, and documentation. The selection of informants employs purposive sampling techniques. The results of this study indicate that the Public Information Disclosure Ambassador program successfully improved accessibility and equitable information, as well as encouraged active participation of the academic community in information dissemination. This study concludes that the New Service Development through this program has proven effective in realizing transparency and openness of information within the UIN Sunan Gunung Djati Bandung environment.